TRADITIONS OF THE POPULATION OF ISHTAKHAN DISTRICT AT WEDDING CEREMONIES (Journal of Universal Science Research, 2025)
This article discusses the customs and traditions of wedding ceremonies among the population of the Ishtikhan district of Samarkand region. This article is based on materials collected during an ethnographic survey during visits to the villages of the Ishtikhan district in 2024. The history, ethnography and ethnogenesis of the Ishtikhan district have not been fully studied to this day. Ishtikhan district, like other districts of the Republic of Uzbekistan, has its own rich ethnographic data, and this data is very close to the Kattakurgan, Payariq, Akdarya and Qoshrabot districts, which border the district territorially. However, some customs are not found in these districts, or even in other regions of Uzbekistan.